Introduction to information systems : essentials for the E-business enterprise - O'Brien, James A. (Boston, Massachusetts : McGraw Hill Education, 2003)
An introduction to information systems, revised to reflect the movement toward enterprise-wide business applications. The text's focus is on teaching the general business manager how to use and manage current IT technologies. The information and case studies in this edition have been updated.
Module I. Foundations Concepts -- Chapter 1 Foundations of Information Systems in Business --Chapter 2. Competing with Information Technology -- Module II. Information Technologies -- Chapter 3. Computer Hardware -- Chapter 4. Computer Software -- Chapter 5. Data Resource Management -- Chapter 6. Telecommunications and Networks -- Module III. Business Applications -- Chapter 7: Electronic Business Systems -- Chapter 8: Electronic Commerce Systems -- Chapter 9: Decision Support Systems -- Module IV: Development Processes -- Chapter 10. Developing e-Business Solutions -- Module V. Management Challenges -- Chapter 11. Security and Ethical Challenges of e-Business -- Chapter 12. Enterprise and Global Management of e-Business Technology.
Includes bibliographical references and index.
Keywords: BUSINESS -- DATA PROCESSING